REGULATION OF PEACEFUL PASSAGE RIGHTS IN THE TERRITORIAL SEA BASED ON THE UNITED NATIONS CONVENTION ON THE LAW OF THE SEA (UNCLOS) - A.A. Gde Agung Dananjaya; Putu Gede Arya Sumerta Yasa (Transpublika Publisher, 2024)
The aim of this research is to conduct a detailed analysis of the regulation of innocent passage rights in territorial waters as outlined in UNCLOS (United Nations Convention on the Law of the Sea) and its practical application. This study utilizes a normative legal research methodology, incorporating legislative and case-based approaches. The findings of this study reveal that the regulation of innocent passage rights in territorial waters is governed by UNCLOS, spanning from Article 17 to Article 32. While the regulation has been extensively addressed, it is not yet fully comprehensive. There are evident ambiguities in the norms that impede the effective implementation of these regulations. The incident involving the entry of American warships into the territorial waters of the People's Republic of China, resulting in conflicts, serves as a prime example of the inadequacies in the regulation of innocent passage rights in territorial waters as outlined in UNCLOS. In this scenario, both nations hold differing interpretations of the norms within UNCLOS.